"I carry her in my heart": An exploration of the experience of bereavement for people with learning disability. (11th January 2018) - Thorp, Nicki; Stedmon, Jacqui; Lloyd, Helen
Abstract : Accessible summary: Four people with learning disability talked about what it was like when someone they cared about had died. They said that it was important they were included, but that it was hard. They said they carried on loving the person after they died and that they missed them. Abstract: Background: Bereavement is a universal experience, yet little research has explored the lived experience of bereavement for people with learning disability (PWLD). Materials and methods: Four PWLD were interviewed about their experience of bereavement. Data were analysed using interpretative phenomenological analysis. Results: Four themes were identified: "Needing to know: Being included, " "Struggling to say: The emotional experience, " "Love after death: A continuing relationship" and "Missing their presence: The wider impact of death." Conclusions: PWLD should have the opportunity to make informed choices about their level of involvement and to develop their emotional experience. PWLD should be supported to develop a continued bond with the deceased and the wider impact of their loss recognised.